2014
DOI: 10.3329/bjar.v38i4.18869
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc, Boron and Molybdenum on the seed yield of carrot (Daucus carota L.)

Abstract: An experiment was conducted at the research field of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Salna, Gazipur during October 2006 to May 2007 to evaluate the effects of zinc, boron, and molybdenum on the seed yield of carrot. The soil of the studied field was deficient in zinc, boron, and molybdenum and represents Salna Series of Shallow Red Brown Terrace under Madhupur Tract (AEZ-28). Four (4) levels each of zinc (0, 2.0, 4.0, and 6.0 kg/ha), boron (0, 1.0, 2.0, and 3.0 kg/ha) and molybdenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
2
2
0
Order By: Relevance
“…The maximum seed yield (14.01q/ha) was associated with foliar application of GA3 @150 ppm (P3) which proved its superiority over other concentrations of GA3 and NAA. Similar results were recorded by Malek et al [10] in carrot, Panwar et al [11], Mohanta et al [24]. The highest seed yield (q/ha) was recorded at F2 (N60 : P40 : K50) and found significantly superior to the rest of the levels.…”
Section: Resultssupporting
confidence: 89%
“…The maximum seed yield (14.01q/ha) was associated with foliar application of GA3 @150 ppm (P3) which proved its superiority over other concentrations of GA3 and NAA. Similar results were recorded by Malek et al [10] in carrot, Panwar et al [11], Mohanta et al [24]. The highest seed yield (q/ha) was recorded at F2 (N60 : P40 : K50) and found significantly superior to the rest of the levels.…”
Section: Resultssupporting
confidence: 89%
“…In this study, harvesting at different ages yielded distinct variations in the biochemical composition of carrot roots. The observed variability in the biochemical constituents of carrot roots as a function of harvest age corroborates earlier reports that the nutritional quality of carrot roots varies with harvest age 33,34 . The corresponding increase in fiber content with an increase in harvest age is consistent with the findings of Paltrinieri 35 who observed that produce harvested too late accumulates excessive fiber.…”
Section: Effect Of Harvest Age On Biochemical Composition Of Carrotsupporting
confidence: 89%
“…Secondly, variations in soil nutrient levels and deficiencies can hinder nutrient uptake by carrot plants, affecting their overall health and productivity [6]. Thirdly, improper timing of harvesting can result in reduced quality and market value due to issues such as lignification, excessive root branching, or loss of moisture content [7]. Fourthly, nutrient imbalances or deficiencies can predispose carrots to diseases and pests, further compromising yield and quality.…”
Section: Introductionmentioning
confidence: 99%
“…The harvesting period has a significant impact on carrot yield. The most crucial elements influencing carrot storage are temperature and root yield, which are determined by harvesting time [15]. Fritz and Habben [16] suggested that carrot should be harvested at proper stage of maturity; otherwise, it will become fluffy and unfit for consumption.…”
Section: Introductionmentioning
confidence: 99%